Strategi Pemasaran Susu Kedelai Rempah di UD. Cakrawala Kelurahan Hewuli, Kecamatan Alok Barat, Kabupaten Sikka - Odilia Siman; Yoseph Yakob Da Rato; Gabriel Otan Apelabi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Soy spice milk (Soya spice) is a drink of soy juice that contains many nutrients, proteins, and oral. The purpose of this study was to find out about the marketing strategies of spice soy milk in UD. Horizon Of Hewuli Village West Alok District sikka Regency. SWOT analysis technique with qualitative approach, consisting of Strenghts, Weakness, Opportunities and Threaths. SWOT analysis aims to maximize strengths and opportunities, but can minimize weaknesses and threats. The IFAS matrix for the total score obtained on the internal factor 2.45 while in the EFAS matrix for the total score obtained by the company on the external factor of 2.75 located in quadrant I (growth), growth, this condition is a favorable situation. Where the company has the opportunity and strength so that it can take advantage of the opportunities that exist